Interpretation of ATR-FTIR spectra of dental adhesives throughout simultaneous polymerization and solvent loss - Arwa Almusa; António H. S. Delgado; Anne Margaret Young (PLoS ONE, 2025)
This study developed new Fourier transform infrared (FTIR) spectroscopy methods to assess effects of drying level on the composition and polymerization kinetics of One‐Step® (OS), OptibondTM Universal (OU) and G‐Bond (GB) dental adhesives. 5 μL of each adhesive were placed in turn on an FTIR, Attenuated Total Reflectance (ATR) accessory, operating at 37ºC. Spectra were generated before, during and after light-curing (20 s, 1000 mW/cm2, 450−470 nm) at 10 s after placement or following 300 s of passive drying (n = 3). Individual spectra of solvents, monomers and fillers, combined with spectral change upon polymerization, were used to generate model spectra and quantify component levels versus time up to 300 s after start of light exposure. Polymerization rates and maximum degree of conversion were derived using a combination of polymer and monomer peaks at 1480 and 1320 cm-1. Inferential analyses included Kruskal-Wallis/Mann-Whitney U using a significance level of 5%. Initial acetone levels were 65, 48 and 50% in OS, OU and GB, respectively, whilst curing at 10 versus 300 s gave final acetone levels of 35, 20 and 32% versus 0, 0 and 10%. With earlier light exposure, monomer reaction rate was reduced but continued for longer leading to final conversions of 88, 86 and 40% versus 61, 66 and 77% for OS, OU and GB, respectively. The FTIR techniques developed could monitor process kinetics and demonstrate the large, highly significant effects of drying method on final polymerized dental adhesive composition and polymerization level.